Multimodal Imaging Technology Effectively Monitors HER2 Expression in Tumors Using Trastuzumab-Coupled Organic Nanoparticles in Patient-Derived Xenograft Mice Models - Wen, Li; Xia, Lei; Guo, Xiaoyi; Huang, Hai-Feng; Wang, Feng; Yang, Xian-teng; Yang, Zhi; Zhu, Hua (Frontiers in Oncology, 2021)
Trastuzumab is a monoclonal antibody targeting human epidermal growth factor 2 (HER2), which has been successfully used in the treatment of patients with breast cancer and gastric cancer; however, problems concerning its cardiotoxicity, drug resistance, and unpredictable efficacy still remain. Herein, we constructed novel organic dopamine–melanin nanoparticles (dMNs) as a carrier and then surface-loaded them with trastuzumab to construct a multifunctional nanoprobe named Her-PEG-dMNPs. We used micro-PET/CT and PET/MRI multimodality imaging to evaluate the retention effect of the nanoprobe in HER2 expression in gastric cancer patient-derived xenograft (PDX) mice models after labeling of the radionuclides 64Cu or 124I and MRI contrast agent Mn2+. The nanoprobes can specifically target the HER2-expressing SKOV-3 cells in vitro (3.61 ± 0.74 vs. 1.24 ± 0.43 for 2 h, P = 0.002). In vivo, micro-PET/CT and PET/MRI showed that the 124I-labeled nanoprobe had greater contrast and retention effect in PDX models than unloaded dMNPs as carrier (1.63 ± 0.07 vs. 0.90 ± 0.04 at 24 h, P = 0.002), a similarity found in 64Cu-labeled Her-PEG-dMNPs. Because 124I has a longer half-life and matches the pharmacokinetics of the nanoparticles, we focused on the further evaluation of 124I-Her-PEG-dMNPs. Furthermore, immunohistochemistry staining confirmed the overexpression of HER2 in the animal model. This study developed and validated novel HER2-specific multimodality imaging nanoprobes for quantifying HER2 expression in mice. Through the strong retention effect of the tumor site, it can be used for the promotion of monoclonal antibody treatment effect and process monitoring.